Arzt-Patienten-Kommunikation und das Problem der Einverständniserklärung in Jeffrey Eugenides’ Roman Middlesex - Mildorf, Jarmila (Jahrbuch Literatur und Medizin)

Charge mentale et violence domestique: une approche des récits de femmes en termes de small stories - Mildorf, Jarmila (Récits de la charge mentale des femmes: small stories II)

Exploring the importance of prior knowledge and verbal cognitive abilities for foreign language learning - Rumlich, Dominik (Cognition and second language acquisition)

Attitudes of German high school students toward different varieties of English - Meer, Philipp; Hartmann, Johanna; Rumlich, Dominik (Applied Linguistics)

Weniger Kompetenz, mehr Resonanz. Contra Position - Rumlich, Dominik (Fremdsprachen Lehren und Lernen)

'The Continent is Isolated‘. Britische Europavorstellungen zwischen Mythos und Wahrheit. - Ehland, Christoph (Die Europäische Union: Konfusion und Vision: Interdisziplinäre Fragestellungen)

Out of the Box and into the Gutter. Rethinking Space in Michael Nicoll Yahgulanaas' Haida Manga Art - Jende, Yvonne Kristin (Artistic Practices of (Un-)Making Place, International and Interdisciplinary Conference)

Introduction: English Linguistics, Learners and the Classroom - Hahn, Charlotte Anna; Mindt, Ilka (Anglistik)
Keywords: General Medicine

Nachwuchs-Café (reloaded): Standortbestimmungen - Rumlich, Dominik; Matz, Frauke (Standortbestimmungen in der Fremdsprachenforschung)

Splendid Consultation: Jochen Buchsteiner reports on Brexit and Britain - Ehland, Christoph (Brexit and the Migrant Voice)

Constructions of a National Threat: Contextualising the Rhetorical Management of the COVID-19 Pandemic in Britain - Tönnies, Merle (Mentalities and Materialities: Essays in Honour of Jürgen Kamm)

Attention to diversity in German CLIL classrooms: Multi-perspective research on students’ and teachers’ perceptions - Siepmann, Philipp; Rumlich, Dominik; Matz, Frauke; Römhild, Ricardo (International Journal of Bilingual Education and Bilingualism)

Bilingualer Unterricht. Aktuelle Herausforderungen und neue Chancen (Fremdsprachen Lehren und Lernen)

Freies Format 2: Nachwuchs-Café (reloaded): Auf dem Weg zur Professur... - Rumlich, Dominik; Matz, Frauke; Juchem-Grundmann, Constanze (Sprache, Kulturen, Identitäten : Umbrüche durch Digitalisierung: 28. Kongress der Deutschen Gesellschaft für Fremdsprachenforschung. Würzburg, 25.-28. September 2019)

Towards Aspect Extraction and Classification for Opinion Mining with Deep Sequence Networks - Kersting, Joschka; Geierhos, Michaela (Natural Language Processing in Artificial Intelligence -- NLPinAI 2020)
This chapter concentrates on aspect-based sentiment analysis, a form of opinion mining where algorithms detect sentiments expressed about features of products, services, etc. We especially focus on novel approaches for aspect phrase extraction and classification trained on feature-rich datasets. Here, we present two new datasets, which we gathered from the linguistically rich domain of physician reviews, as other investigations have mainly concentrated on commercial reviews and social media reviews so far. To give readers a better understanding of the underlying datasets, we describe the annotation process and inter-annotator agreement in detail. In our research, we automatically assess implicit mentions or indications of specific aspects. To do this, we propose and utilize neural network models that perform the here-defined aspect phrase extraction and classification task, achieving F1-score values of about 80% and accuracy values of more than 90%. As we apply our models to a comparatively complex domain, we obtain promising results.

Gattung und Geschlecht: Konventionen und Transformationen eines Paradigmas

The Black British Bildungsroman: Gender-specific Plot Models? - Tönnies, Merle (Gattung und Geschlecht: Konventionen und Transformationen eines Paradigmas)

Bilingualer Unterricht. Aktuelle Herausforderungen und neue Chancen: Zur Einführung in den Themenschwerpunkt [koordiniert von B. Diehr & D. Rumlich] - Diehr, Bärbel; Rumlich, Dominik (Fremdsprachen Lehren und Lernen)

Review of Liss Kerstin Sylvén (Ed.). (2019). Investigating content and language integrated learning. Insights from Swedish high schools - Rumlich, Dominik (Journal of Immersion and Content-Based Language Education)

"There". Die Verwendung von "there" im authentischen Englisch, im Englisch von Lernenden und in Schulbüchern - Mindt, Ilka (Sprachwissenschaft und Fremdsprachendidaktik: Konstruktionen und Konstruktionslernen)